Представники ряду Chiroptera в колекції Музею природи Харківського національного університету ім. В. Н. Каразіна - Ільюхін, Ю. (Theriologia Ukrainica, 2018)
У колекції Музею природи на наш час зберігається 139 зразків кажанів, які належать до 18 видів, 11 родів та 3 родин. Почали збирати цю колекцію ще у 1834 році (2 опудала Nyctalus noctula). Цікаві також старі експонати з тропічних зон — опудало Macroglossus minimus (1865 р.) з о-ва Ява, опудало Pteropus vampirus (бл. 1864 р.) та скелет Pteropus poliocephalus (1869 р.). Серед фондової частини колекції найбільше матеріалу (67 зі 112 зразків) походить з Харківської обл. (Харківський, Зміївський, Чугуївський, Ізюмський р-ни) України, здобуті у 1930–60-х рр. В МПХУ зберігаються цінні зразки червонокнижних видів — Myotis dasycneme, Nyctalus lasiopterus, N. leisleri, Miniopterus schreibersii. Серед колекторів — три відомі професори, які в різний час були завідувачами кафедрою зоології Харківського університету — О. Брандт, В. Станчинський, І. Волчанецький. Ця колекція є однією з найдавніших в Україні і має значну наукову цінність. Дано повний перелік зразків з усіма (крім колекційних номерів) даними. Експозиційна частина колекціі виставлена в залах для огляду, а наукова зберігається у фондовому приміщенні. The collection of the Museum of Nature currently hosts 139 bat specimens of 18 species belonging to 11 genera of 3 families. The beginnings of the collection dates back to 1834 when 2 stuffed Nyctalus noctula were acquired. High historical and scientific value have the specimens of Macroglossus minimus collected in 1865 in Java, the specimens of Pteropus vampirus collected around 1864, and the skeleton of Pteropus poliocephalus from 1869. The main part of the collection consists of specimens from the Kharkiv region, Ukraine (67 of 112 specimens) collected in the 1930s–60s. Among them are valuable specimens of currently rare species listed in the national Red Data Book: Myotis dasycneme, Nyctalus lasiopterus, N. leisleri, and Miniopterus schreibersii. Three prominent professors, O. Brandt, V. Stanchinsky, I. Volchanetsky, who were head of zoology department of Kharkiv University during different periods, contributed to the collection. The collection is one of the oldest in Ukraine and has a high scientific value. The checklist of the collection with all original data (except of collection numbers) are provided. Part of the collection is exhibited, while the other part is deposited in the scientific storage facility.